Did we learn something positive out of the COVID-19 pandemic? Post-traumatic growth and mental health in the general population - Giulia Menculini; Umberto Albert; Valeria Bianchini; Claudia Carmassi; Giuseppe Carrà; Francesca Cirulli; Bernardo Dell’Osso; Michele Fabrazzo; Francesco Perris; Gaia Sampogna; Maria Giulia Nanni; Maurizio Pompili; et al. (European Psychiatry, 2021)
Abstract